2005
DOI: 10.1074/jbc.m412514200
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Interactions between the Amino Terminus of G-protein βγ Subunits and the Catalytic Domain of Phospholipase Cβ2

Abstract: Activation of G-protein-coupled receptors releases the G␤␥ subunit from G␣-GTP, leaving G␤␥ free to interact with effector molecules such as enzymes or ion channels (1-3). A particular group of enzymes regulated by G␤␥ belong to the phosphoinositide-specific phospholipase C␤ (PLC␤) 1 class. Once activated, PLC␤ cleaves phosphatidylinositol 4,5-bisphosphate (PIP 2 ) into the two second-messengers, diacylglycerol and inositol 1,4,5-trisphosphate. All PLC␤ isoforms have an N-terminal pleckstrin homology (PH) doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 35 publications
0
47
0
Order By: Relevance
“…Additional regions found to be important for the Gβγ -activation of PLC-β2 (strands 2d and 6d) are in light blue [68]. The second-binding site for PLC-β2 found in the N-terminal region of Gβ are in magenta [71]. The Gγ subunit is colored in dark grey.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Additional regions found to be important for the Gβγ -activation of PLC-β2 (strands 2d and 6d) are in light blue [68]. The second-binding site for PLC-β2 found in the N-terminal region of Gβ are in magenta [71]. The Gγ subunit is colored in dark grey.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was found that the geranylgeranylated moiety attached to the C-terminal segment of the Gγ, which is proximal to the membrane and anchors Gβγ to lipids, binds to the PLC-β2 [69,70]. Moreso, Smrcka and colleagues, proposed that the 23-27 region of the N-terminal helix of the Gβ subunit was a second PLC-β binding site maintaining the enzyme outside the propeller in an inhibition state [71]. Thus, it appears that the top and the edge sides of the propeller is the region of Gβγ which binds to PLC-β and promotes activation.…”
Section: Plc-β2 Binding Site(s) In Gβγmentioning
confidence: 99%
See 3 more Smart Citations